The Relationship between Maximum Oxygen Volume and Short Term Memory in Students of the Faculty of Sports Science, Medan State University - David Simangunsong (Jurnal EduHealth, 2020)
Short term memory is a storage system for holding small amounts of information with a duration of 15-30 seconds for about 7 things. Regular exercise can increase a person's VO2max value. A good VO2max will cause an increase in the hormones BDNF, IGF-1 and FGF. The increase in these hormones can increase the stimulation of neurogenesis in the dentate gyrus of the hippocampus and in the subventricular zone of the lateral ventricles so as to produce good short-term memory function as well. This study aims to determine the relationship between VO2max and short-term memory in students of the Faculty of Sports Science, Medan State University. This research is an observational analytic study with a cross sectional design. The population of this study were students of the Faculty of Sports Science, Medan State University. The sample in this study were 40 students selected by purposive sampling technique. VO2max was measured using the 12 minute Cooper Test and short term memory was measured using the Digit Symbol Substitution Test. Data analysis in this study used Fisher's test and found that there was no relationship between VO2max and short-term memory in students of the Faculty of Sports Science at Medan State University with p = 0.723. There is no relationship between VO2max and short-term memory in students of the Faculty of Sports Science, Medan State University.